From community to corporate governance: Ecotourism destination management transition at Bronjong River, Cipadang Village, Pesawaran - Andika Gilang Nurmoyo; Evi Novianti; Yunus Winoto; Desmala Sari; Dina Oktavia (Universitas Merdeka Malang, 2026)
Governance transitions in nature-based tourism destinations remain underexplored, particularly in contexts where community-based ecotourism (CBET) arrangements collapse due to institutional failure and land tenure complexity. This study examines the governance transition at Bronjong River ecotourism destination, Cipadang Village, Pesawaran Regency, Lampung Province, from community-based management under Pokdarwis Pelangi Cipadang to corporate-led management under PT Perkebunan Nusantara (PTPN) I Regional 7. Employing a descriptive qualitative approach with a case study design, data were collected through semi-structured interviews with 11 informants representing five stakeholder groups, participatory observation, and documentation study. Findings reveal that institutional failure, manifested through weak financial accountability, illegal levies, and unmet contractual obligations, triggered the collapse of community-based governance and subsequent corporate takeover. The transition produced paradoxical outcomes: local operational workers from five buffer villages, UMKM operators, and tourists reported improved conditions under PTPN management, while the village government and BUMDes experienced institutional and economic marginalization. These findings challenge dominant assumptions that community-based governance is inherently superior to corporate alternatives, demonstrating that institutional capacity and accountability mechanisms are more decisive determinants of governance quality. This study contributes to destination management literature by providing empirical evidence of hybrid corporate-community governance dynamics in rural Indonesian river tourism.